Making tricot data FAIR, from collection to reuse - 1000FARMS Platform (Bioversity International and International Center for Tropical Agriculture, 2025)
The Alliance of Bioversity and CIAT is enhancing the interoperability and reuse of tricot data through the development of FAIR-aligned tools and practices. By introducing standard operating procedures, ontology annotations, and improved metadata fields in ClimMob, the team supports seamless integration of trial datasets across crops, sites, and projects. The improvements allow more consistent, discoverable, and impactful use of on-farm data, contributing to open science through public repositories like GitHub and Zenodo. These efforts enable researchers and partners to generate insights more efficiently and ensure that data collected from participatory trials is easier to access, understand, and reuse. The work is part of 1000FARMS and supported by the Bill & Melinda Gates Foundation.